The impact of the African Charter and Women's Protocol in selected African states (Pretoria University Law Press (PULP), 2012)
The impact of the African Charter and Women's Protocol in selected African states 2012 ISBN: 978-1-920538-11-8 Pages: x 212 Print version: Available Electronic version: Free PDF available